2023
DOI: 10.1038/s41598-023-28442-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided design and 3-dimensional artificial/convolutional neural network for digital partial dental crown synthesis and validation

Abstract: The current multiphase, invitro study developed and validated a 3-dimensional convolutional neural network (3D-CNN) to generate partial dental crowns (PDC) for use in restorative dentistry. The effectiveness of desktop laser and intraoral scanners in generating data for the purpose of 3D-CNN was first evaluated (phase 1). There were no significant differences in surface area [t-stat(df) = − 0.01 (10), mean difference = − 0.058, P > 0.99] and volume [t-stat(df) = 0.357(10)]. However, the intraoral scans were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In 2023, Chau et al (2023) and Ding et al (2023a) demonstrated that the 3D GAN and 3D-DCGAN networks are beneficial in automatically designing biomimetic dental restorations by learning the occlusal anatomic features of similar remaining teeth. Farook et al (2023) created a new 3D dental prosthetic dataset for 3D convolutional neural network (3D-CNN) training purposes, as virtual data were successfully used in both open-source and commercial CAD workflows to create tooth preparations for machine learning (ML) in restorative dentistry. 3D deep learning (DL) was able to accurately produce inlays and onlays for suitable tooth preparations ( Farook et al, 2023 ).…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2023, Chau et al (2023) and Ding et al (2023a) demonstrated that the 3D GAN and 3D-DCGAN networks are beneficial in automatically designing biomimetic dental restorations by learning the occlusal anatomic features of similar remaining teeth. Farook et al (2023) created a new 3D dental prosthetic dataset for 3D convolutional neural network (3D-CNN) training purposes, as virtual data were successfully used in both open-source and commercial CAD workflows to create tooth preparations for machine learning (ML) in restorative dentistry. 3D deep learning (DL) was able to accurately produce inlays and onlays for suitable tooth preparations ( Farook et al, 2023 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“… Farook et al (2023) created a new 3D dental prosthetic dataset for 3D convolutional neural network (3D-CNN) training purposes, as virtual data were successfully used in both open-source and commercial CAD workflows to create tooth preparations for machine learning (ML) in restorative dentistry. 3D deep learning (DL) was able to accurately produce inlays and onlays for suitable tooth preparations ( Farook et al, 2023 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Results of the Quadas-2 assessment of included studies are presented in Table 6. A total of 18.3% of studies (7/38) were identified as low-risk of bias studies [8,25,29,33,43,45,46], whereas 52.6% (20/38) and 28.9% (11/38) of included studies were identified as studies with high [12-15,17-19,20-22,26,28,30,34-38, 42,44] and unclear [4,5,16,23,24,27,31,32,39,40,46] risk of bias, respectively. Inter-rater and intra-rater reliability of the Cohen kappa were 0.8831 and 0.9232, respectively, which reflect near-perfect reliability.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Initially, studies focused on traditional convolutional neural networks (CNNs) such as U-Net for caries detection and localization [74,75]. Subsequent progress led to the development of more sophisticated architectures, including a 3D-CNN for generating partial dental crowns, demonstrating improved validation accuracy and sensitivity [76]. The evolution continued with the introduction of self-training-based methods, leveraging unlabeled data for student model training, offering computational and performance gains over traditional supervised learning [77].…”
Section: Strengthsmentioning
confidence: 99%